(untitled) (Global Journal of Human-Social Science, 2020)
An investigation was carried out to find out the conditions conducive to deep sleep and to work out a deep simulating technique for discovering peace in waking state. The results showed that till the element of I-ness and my-ness along with an effort to sleep exists, sleep does not come. The moment these elements disappear on their own, sleep sets in. In the deep sleep, one is in extreme peace state as his association with the body and its associations with the world is completely cut off. Besides the sleeper also goes beyond time, mind and sense of doership and enjoyership. The experience of the deep sleep showed that the peace is inside us but needs to be discovered. The deep sleep simulating technique is worked out to discover peace even in the waking state consisted of sitting in utter silence for ten to fifteen minutes to start with, in a nobody state without any sense of ownership of body and its associations or relations at a belief level. While sitting in silence, one does not do anything nor does he expect anything to get or lose and accepts the happenings as such with an open mind without any reservation , in other words with an indifferent attitude, thus paving the way to go beyond likes and dislikes of mind. This silence technique was tested on twenty adults in a yoga class conducted during 2018 and 2019 in the morning hours. The results showed that all of them experienced rest, contentment and peace.